(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The purpose of the research is to reveal the current problems of the economic security of chemical industry enterprises and to determine their solutions. Modern approaches and mechanisms related to ensuring economic security is considered. The progressive international experience of strengthening the economic security system is reviewed. The importance of adapting the organization of economic security in chemical enterprises to the requirements of the time was noted. The relevance of the preparation and application of modern mechanisms of the economic security system in chemical industry enterprises is given in the conditions of global threats. The importance of complex measures in the direction of strengthening the provision of raw materials for chemical enterprises is substantiated.